Invisible labour with Visible effect: The Impact of Unpaid Work on Women Health and Wellbeing - Akeel Naveed Raja, Dr. Ganesh Digal (South Eastern European Journal of Public Health, 2025)
Unpaid labour refers to the essential domestic and caregiving work carried out primarily by women without financial compensation. This includes household chores, child-rearing, elderly care, and other duties that contribute significantly to the well-being of households and communities but are not formally recognized or rewarded in economic systems. Despite its importance, unpaid work remains largely invisible and undervalued. This study explores how unpaid labour affects women’s physical, mental, and social well-being. The physical impacts of unpaid labour are significant, with women experiencing chronic health problems such as back pain, musculoskeletal disorders, and fatigue due to the repetitive and often strenuous nature of domestic tasks. In addition to these physical challenges, the mental and emotional toll of managing unpaid labour is substantial. Women frequently report experiencing high levels of stress, anxiety, depression, and emotional burnout as they juggle household responsibilities, caregiving, and other life roles. This mental strain is exacerbated by feelings of isolation, guilt, and a diminished sense of self-worth, as their contributions often go unacknowledged. Unpaid labour also negatively affects women’s social lives. The overwhelming time commitments leave little room for personal development, social interaction, or self-care, leading to social isolation and strained relationships. Furthermore, the burden of unpaid labour limits women’s access to healthcare, as they often delay seeking medical attention due to time constraints and caregiving duties. The findings of this study emphasize the critical need to recognize unpaid labour and address its effects on women’s health and well-being. Structural changes, such as redistributing domestic responsibilities and providing greater support for women, are necessary to reduce the negative impacts of unpaid labour. By acknowledging the importance of unpaid work, society can improve women’s overall health, quality of life, and well-being, fostering a more equitable and supportive environment for all.